INTERLANGUAGE ANALYSIS OF SYNTACTIC AND DICTION ERRORS FOUND IN THESES WRITTEN BY MAGISTER STUDENTS - Handayani, Rindu; Ihsan, Diemroh; Mirizon, Soni (International Journal of Indonesian Education and Teaching (IJIET), 2019)
Postgraduate students are expected to show more advanced writing skill than others. However, the writer observed that they still made some errors in their thesis writing. Having reread the theses written by graduate students, Linguistic Surface Category and Surface Strategy Taxonomy proposed by Dulay, Burt & Krashen were utilized to analyze the data. It was found that syntactic errors (89%) such as subject-verb agreement (15.42%), tenses (15.71%), redundancy (13.14%), article (7.71%), and pluralization (6.28%) are the most frequent errors occured. While lexical errors (11%) such as wrong selection of verb (5.14%) and adjective (3.14%) also still made by graduate students. The study revealed that intralingual interference still be the cause of the blunders in writing a thesis.  It is hoped that the present study could  initiate university students to contemplate that self-correction and self-awareness in making errors in scholarly writing are essential. Emphasizing more assignments in academic writing can be applied by the lecturers of higher education know  students’ ability and  train students to write academically. Faculty of teacher training of education should afford students with seminars and workshop  of  academic writing to motivate them to write and enhance their knowledge about academic writing.DOI: doi.org/10.24071/ijiet.2019.030110